Acoustic target strength of capelin measured by single-target tracking in a controlled cage experiment - Jørgensen, Roar; Olsen, Kjell (ICES Journal of Marine Science, 2002)
Knowledge of the acoustic target strength (TS) of capelin, Mallotus villosus (Müller), is important to scale integrator outputs for use in acoustic surveys, but experimental measurements of capelin TS are scarce. This paper reports a new ex situ experiment on capelin TS. Small groups of the fish were kept in a large sea cage that allowed them to swim freely between 4.5 and 10 m deep. TS measurements were made vertically with a scientific split-beam echosounder. Differences in behaviour could induce at least a 5 db change in TS owing to changes in tilt angle. The observed mean TS for capelin from the local Balsfjord stock was >1 db higher than expected from the TS–length relationship for Barents Sea capelin used during abundance estimation.